The Hype Cycle of Working Memory Training. (October 2019) - Redick, Thomas S.
Seventeen years and hundreds of studies after the first journal article on working memory training was published, evidence for the efficacy of working memory training is still wanting. Numerous studies show that individuals who repeatedly practice computerized working memory tasks improve on those tasks and closely related variants. Critically, although individual studies have shown improvements in untrained abilities and behaviors, systematic reviews of the broader literature show that studies producing large, positive findings are often those with the most methodological shortcomings. The current review discusses the past, present, and future status of working memory training, including consideration of factors that might influence working memory training and transfer efficacy.